2005
DOI: 10.1111/j.1365-2486.2005.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Below‐ground responses of silver birch trees exposed to elevated CO2 and O3 levels during three growing seasons

Abstract: Field-growing silver birch (Betula pendula Roth) clones (clone 4 and 80) were exposed to elevated CO 2 and O 3 in open-top chambers for three consecutive growing seasons (1999)(2000)(2001). At the beginning of the OTC experiment, all trees were 7 years old. We studied the single and interaction effects of CO 2 and O 3 on silver birch below-ground carbon pools (i.e. effects on fine roots and mycorrhizas, soil microbial communities and sporocarp production) and also assessed whether there are any clonal differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 78 publications
6
49
0
Order By: Relevance
“…Soil respiration decreased beneath the trembling aspen (Coleman et al 1996), Pinus taeda L. seedlings (Edwards 1991), and wheat and soybean (Islam et al 2000) after being exposed to O 3 treatments. In contrast, soil respiration increased under O 3 stress in the experiment with silver birch (Betula pendula Roth) (Kasurinen et al 2005). These inconsistent results make it difficult to assess the impact of elevated O 3 concentration on C cycle processes that critically influence plant growth as well as climate change (Andersen and Rygiewicz 1995).…”
mentioning
confidence: 72%
“…Soil respiration decreased beneath the trembling aspen (Coleman et al 1996), Pinus taeda L. seedlings (Edwards 1991), and wheat and soybean (Islam et al 2000) after being exposed to O 3 treatments. In contrast, soil respiration increased under O 3 stress in the experiment with silver birch (Betula pendula Roth) (Kasurinen et al 2005). These inconsistent results make it difficult to assess the impact of elevated O 3 concentration on C cycle processes that critically influence plant growth as well as climate change (Andersen and Rygiewicz 1995).…”
mentioning
confidence: 72%
“…However, in ponderosa pine (Pinus ponderosa), the total fungal and bacterial biomasses increased at low O 3 levels, and the total microbial biomass decreased at high O 3 levels, compared to the biomasses under the control treatment (Scagel and Andersen, 1997). O 3 has also been reported as having only slight effects on soil biomass in field-grown silver birch exposed to eO 3 in OTCs for 3 years (Kasurinen et al, 2005). O 3 may shift microbial structure without altering total microbial biomass, as has previously been found under eCO 2 (Phillips et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a significant discrimination of sole-carbon source utilization patterns was observed for the wheat rhizosphere soil but not for the bulk soil, and the functional diversity of the rhizosphere microbial communities was reduced under eO 3 (Chen et al, 2009). Also, a few studies at the Aspen FACE site (Larson et al, 2002;Phillips et al, 2002;Chung et al, 2006;Holmes et al, 2006;Zak et al, 2007) and with open-top chambers (Kasurinen et al, 2005) or mesocosms (Kanerva et al, 2008) indicated that eO 3 altered the functional diversity, structure and/or metabolic potential of soil microbial communities. In this study, our results did not fully support the above hypothesis that eO 3 would alter the overall functional diversity and structure of rhizosphere microbial communities.…”
Section: Shifts Of Functional Gene Representation Under Eo 3 X Li Et Almentioning
confidence: 99%
“…In recent years, most studies on the effect of eO 3 on rhizosphere microbial communities were largely based on open-top chambers, and the results mainly focused on the changes of microbial biomass and structure by phospholipid fatty acid analysis, denaturing gradient gel electrophoresis methods (Kasurinen et al, 2005;Chung et al, 2006;Kanerva et al, 2008), and/or singlestrand conformation polymorphism method (Dohrmann and Tebbe, 2005). Those studies indicated that eO 3 had little or significant effects on soil microbial communities with different plants/ecosystems.…”
Section: Introductionmentioning
confidence: 99%